PERMEABELITAS BETON KEKUATAN TINGGI - Rahman, Masril
Due to its denseness, the phenomena of High Strength Concrete and Normal Strength Concrete is absolutely different, especially High Strength Concrete has lower void ratio. The impermeability of concrete is explained by its coefficient of permeability (K) and this has smaller value for High Strength Concrete. The experimental coefficients of High Strength Concrete made of materials from Indonesia, without additives, were reported in this thesis. All the test procedures followed DIN-1048 Standard. The absorption of High Strength Concrete which done by immersing the specimens in air Lighted tank filled by water also reported The percentage of absorption is expressed by ratio of weight of infiltrated water to the dried specimen. These specimens were made in three different interval of compaction time, i.e. 30, 60 and 90 minutes using vibrating table. The absorption itselves were also tested in three condition of the immersion water level, that is 1/3, 2/3 and full immersion. So far, the amount of each materials in the specimen is measured. Finally all the experiments data were compared to the experiments data from others and also using the exist formulas to determine the coefficient of permeability. It shows that High Strength Concrete has lower coefficient of permeability (the water penetration is approximately 2.09 %)